The Path Intended and the Path Taken: A Rejoinder to Dr. O'Connell. Issue 1 (2nd January 2020) - Kessler, Molly Margaret; Graham, S. Scott
ABSTRACT: With the goal of increasing interdisciplinary dialogue, the authors engage Dr. O'Connell's response to "Terminal node problems: ANT 2.0 and prescription drug labels." Specifically, the authors aim to address the questions and concerns raised by Dr. O'Connell as well as offer suggestions for future research that builds on the insights that emerge from this interdisciplinary dialectic.